Geochemical Evaluation of Heavy Metals Soil Pollution in Al-Hayy District Affected by Agriculture Activities: a case study - AL-Najjar , Rand Deyaa; Hussain, Tariq Abed; Al Obaidy, Abdul Hameed M.J. (Iraqi Journal of Science, 2024)
This research aims to assess trace elements of contamination by agricultural soils in the Al-Haye district. Soil samples were collected from a selected agricultural area near the banks of the Tigris River, and trace elements (Ag, As, Ba, Cd, Co, CR, Cu, Fe, Hg, Mn, Ni, Pb, Se, V, Zn, Zr, Pb, Se, V, Zn, Zr), pH, electrical conductivity, and organic matter were identified in soil samples. The pH of the soil sample ranged between 7.7 and 7.6, which is equivalent to the pH of the sub-alkalis (7.3). The organic matter content is 1.8433%; this range of organic matter is between 1.56 and 1.98. The average soil conductivity was 995.37 ug/cm. The level of trace contamination was found in soil samples as follows: Fe> Mn> Ba> Cr> Ni> Zr > V > Zn > Cu> Pb> Co> Ag >Cd> Hg> Se. Soil samples contained concentrations of Cd, Cr, Cu, Mn, and Ni much higher than the global average of unpolluted soil concentrations. In contrast, only half of the zinc samples exceeded the calculated average global average of the unpolluted soil, and lead had values within the international level of the unpolluted soil. The study area needs an environmental management system to manage and treat soil pollution in urban areas.